Socio-Economic Life Development Of Transmigrants In Karya Mulya Village, Rambang District, Central Kapak, Prabumulih City 1986-2016 - Wulan Wulan; Alian Alian; Yunani Yunani (Criksetra: Jurnal Pendidikan Sejarah, 2018)
This research entitled '' Development of Social Economic Life of Transmigrant Community in Desa Karya Mulya Sub-district of Rambang Kapak Tengah Town of Prabumulih year 1986-2016 '' as for the purpose of this research is to know the development of social life of transmigrant community in Prabumulih Karya Mulya city year 1986-2016 and to know the development of the economic life of transmigrant communities in the village of Karya Mulya Prabumulih city in 1986-2016. The methodology used in this study is the historical method with steps: heuristic, source critic, interpretation, historiography and in-depth interviews with community figures in the village of Karya Mulya. While the approach used is the sociology and economic approach, based on the results of research, it is found that the social life of the community of Mulya covers the Social Interaction, the Associative Process and the Dissociative Process as well as the development of the village of Karya Mulya seen after the city of Prabumulih became the definitive city, for the village of Karya Mulya easier to manage the Administration due to the distance is quite close. While the development in the field of economy includes the development of palm oil, rubber farming and seasonal crops covering the development of production and distribution of this is in line with the increasing level of welfare of the people of the village of Karya Mulya evidenced by the number of Permanent buildings.